Use of food additives in specialized fruit and vegetable foods for child and diet food - Benderska (Dushchak), Olga; Levkivska (Muzika), Tetiana; Bessarab, Alexander (My University, 2021)
Modern market research baby food show that in recent years the situation in the country in baby food area and provided child population corresponds to ation products are evaluated as unsatisfactory. Need children in different types of food products of domestic production at present satisfies is in the range of 9 to 54% depending on bridges from the main type used of raw materials.
Keywords: дитяче харчування; консервування; food for children; canning; кафедра технології консервування